Hubungan Kompetensi Pedagogik Guru Dengan Hasil Belajar Siswa Kelas VIII SMP Negeri 4 Kota Ternate Pada Konsep Getaran Dan Gelombang - hamid, fatma; Sahjat, Sumarni; Saprudin, Saprudin; Rahman, Nurdin Abd; Buaja, Taslim; Husen, Ria Rizkia (Universitas Khairun, 2025)
This study aims to determine the correlation between teacher pedagogical competence and student learning outcomes in physics subjects at SMP Negeri 4 Ternate City. This study uses a quantitative approach. The data collection technique uses a random sampling technique with a correlational research design, with a population of 240. The sample in this study was 22 students of class VIII-5 SMP Negeri 4 Ternate City. Data were obtained using the Test technique for variable Y and non-test (questionnaire) for variable X. The research instrument in the form of data in the form of checklist guidelines, questionnaires for students that have been tested for validity and reliability, documentation. Data analysis uses normality tests, homogeneity tests, linearity tests, hypothesis tests consisting of one independent variable and one dependent variable. The results of this study obtained a questionnaire used to collect data validated with the product Moment correlation formula obtained 11 valid items of the tested statements. The reliability test of the questionnaire was also carried out on the 11 items of the teacher's professionalism statement using the Alpha method so that a reliability coefficient of 0.93 was obtained. teacher pedagogical competence data obtained the highest score of 55 and the lowest score of 45 with an average of 51.33, a variance of 15.25, and a standard deviation score of 3.90, and student learning outcome data obtained the highest score of 47 and the lowest score of 28 with an average of 17.72, a variance of 484.7, and a standard deviation score of 22.02. The statistical results obtained the product moment correlation between teacher professionalism and learning outcomes obtained 3.79 1.895 means Ha is accepted and Ho is rejected, meaning that there is a relationship between teacher pedagogical competence and student learning outcomes, in other words between teacher pedagogical competence and learning outcomes there is a very strong correlation, this means that teacher pedagogical competence greatly influences student learning outcomes.